Light emission of flame-generated TiO2 nanoparticles: Effect of IR laser irradiation. (January 2021) - De Iuliis, Silvana; Dondè, Roberto; Altman, Igor
Highlights: Measurements of light emission of titania nanoparticles in flame spray apparatus heated by low-energy IR laser pulses. Detection of the behavior of temperature of particles with and without laser irradiation versus laser fluence (starting from very low values of laser fluence). Investigation of the behavior of the Urbach energy of titania nanoparticles affected by IR laser. Evauation of the refractive index of the irradiated titania nanoparticles at the excitation wavelength. Abstract: The aim of this work is the analysis of the evolution of titania nanoparticles based on their light emission spectra. Measurements are performed during the synthesis of the nanoparticles in a flame spray, which is irradiated by a pulsed IR laser. Due to the relatively high energy band gap of titania of about 3 eV, the observed substantial light absorption at the laser wavelength of 1.064 μm, i.e. within the region of titania transparency, makes our study novel and interesting. Laser-induced light emission at different laser fluences is compared with spontaneous light emission from titania nanoparticles in flame. For signal processing, Wien plot is introduced to obtain the particle temperature. A peculiar feature of the temperature difference of the irradiated and nonirradiated particles versus laser fluence is obtained. Three well-defined regions of this fluence curve are observed and discussed with a particular attention on the plateau-like behavior at very low laser fluence, followed by a linear increase. An anomalously high titania absorption is inferred in the linear region. The increase of the Urbach energy is speculated to account for the change in the optical properties of titania nanoparticles. It is related to structural defects, and, therefore, the presence of energy levels in the forbidden band due to the particular synthesis condition and/or induced by laser irradiation.